SUPEREXPLORAÇÃO DA FORÇA DE TRABALHO, CRISE MUNDIAL E GOLPE DE ESTADO NO BRASIL - Terçália Suassuna Vaz Lira (Universidade Federal do Maranhão, 2018)
This study was made to analyze the exploitation of the workforce in the dependent peripheral economies and also the current global crisis scenario and how they imply in the political crisis and coup underway in Brazil. It was sought through a review of the literature to look at the Marxist theory of dependency in order to identify the conditions that allow explaining the current setbacks that have been taking place in the Latin American scenario in which the coup in Brazil stands out. The exploitation of the working force in our current scenario is linked to the ﬁnancial capital valuation process and its biggest impacts will occur in the dependent economies in order to pressure them to redeﬁne their economic, political and labor order so they can answer to global capitalism determinations.